If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -50 = 10x + 73 Reorder the terms: -50 + 6x = 10x + 73 Reorder the terms: -50 + 6x = 73 + 10x Solving -50 + 6x = 73 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -50 + 6x + -10x = 73 + 10x + -10x Combine like terms: 6x + -10x = -4x -50 + -4x = 73 + 10x + -10x Combine like terms: 10x + -10x = 0 -50 + -4x = 73 + 0 -50 + -4x = 73 Add '50' to each side of the equation. -50 + 50 + -4x = 73 + 50 Combine like terms: -50 + 50 = 0 0 + -4x = 73 + 50 -4x = 73 + 50 Combine like terms: 73 + 50 = 123 -4x = 123 Divide each side by '-4'. x = -30.75 Simplifying x = -30.75
| -0.7x+0.8x+8=-2 | | 2ln(x)=ln(x+6) | | 3x=(4x-15) | | 2y+8y-3=x | | 5p-4=2p+12 | | 6.9x-6+x-1.6= | | 31=5t+6 | | 180+17n=350 | | 8-24=3y-2 | | 0.7+0.8+8=-2 | | V^2=U^2+2AH | | s=5r^3t | | 1/3x+6=-4 | | 3m-3=24 | | S=7+4s | | 7b+5-7b-2=8 | | 1/2x-1=-5 | | 3c+(c+12)=124 | | 4.5/5 | | 20=S+13-4s | | 3c+(c+12)=24 | | 0.25x+7.5-0.75x=3 | | y=za | | -5(6(a)+2)=-15 | | 1/9+4=5 | | 2x=11+6 | | 3/8z-1=5 | | 0.24/48 | | 7x-3-6x=5+5x-13 | | -1.9x+4.1x=8.8 | | 8(d)-4(d)+5=13 | | 1-7c=0 |